Compulsory treatment of physical illness under MHA 1983 - Wheeler, Robert (Journal of medical ethics, 2022)
Taken together, Sections 145 and 63 of the Mental Health Act 1983 (MHA) provide for treatment without consent of physical illness ancillary to the mental disorder with which a patient presents. On a daily basis, clinicians make both the decision that the Act’s authority can be applied to their patient’s case, and that it should be applied. But in the unusual circumstances where there is uncertainty as to the applicability of the MHA to the ancillary treatment of physical illness, the assistance of a court may be sought. In so doing, the law (and thence the courts) may justify compulsion but never prescribes it; the clinician is presented with authority that he or she could use but is left to decide whether it should be employed. This paper explores how the clinical question is set before the court, and whether the distinction between symptom, manifestation and consequence is sufficiently understood. This has important consequences in the context of self-neglect and its close cousin self-harm: the question whether the relevant ailment was attributable to or exacerbated by neglect or self- inflicted harm will determine whether compulsion under the MHA is applicable; and furthermore, whether or not compulsion is clinically acceptable.